2021
DOI: 10.7717/peerj.12455
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific covariance between metabolic rate, behaviour and morphology in the ground beetle Carabus hortensis

Abstract: Background Individuals within the same species often differ in their metabolic rates, which may covary with behavioural traits (such as exploration), that are consistent across time and/or contexts, and morphological traits. Yet, despite the frequent occurrence of sexual dimorphisms in morphology and behaviour, few studies have assessed whether and how sexes differ in metabolic trait covariances. Methods We investigated sex-specific relationships among resting or active metabolic rate (RMR and AMR, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The relationship between MR and risk‐taking behavior in Australian field crickets Teleogryllus oceanicus was found negative in females, whereas no clear association between all traits was found in males (Moschilla et al, 2019 ). In the study on ground beetles, Carabus hortensis done by Yarwood et al ( 2021 ) both male and female active MR was slightly positively related to exploratory behavior. However, the relationships between active MR and exploration were m b dependent in males and temperature dependent in females indicating the different source of this association (Yarwood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The relationship between MR and risk‐taking behavior in Australian field crickets Teleogryllus oceanicus was found negative in females, whereas no clear association between all traits was found in males (Moschilla et al, 2019 ). In the study on ground beetles, Carabus hortensis done by Yarwood et al ( 2021 ) both male and female active MR was slightly positively related to exploratory behavior. However, the relationships between active MR and exploration were m b dependent in males and temperature dependent in females indicating the different source of this association (Yarwood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…In the study on ground beetles, Carabus hortensis done by Yarwood et al ( 2021 ) both male and female active MR was slightly positively related to exploratory behavior. However, the relationships between active MR and exploration were m b dependent in males and temperature dependent in females indicating the different source of this association (Yarwood et al, 2021 ). Videlier et al ( 2019 ) showed a positive association between SMR and proactivity in male fruit flies Drosophilla melanogaster , whereas any association was absent in females.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the mass-dependence of thermal acclimation capacity was associated with modest sex differences in thermal plasticity within species that exhibited sexual size dimorphism-potentially due to heavier organisms having greater thermal inertia in response to temperature change [27]. Moreover, males and females have also been shown to differ in their relationship between physiology and behaviour [29][30][31], suggesting that temperatureinduced effects on physiological traits may exert sex-specific effects on behaviour. However, whether the effects of temperature on individual-level variation are sex-specific remains largely uninvestigated.…”
Section: Introductionmentioning
confidence: 99%